2021
DOI: 10.3389/fnut.2021.704619
|View full text |Cite
|
Sign up to set email alerts
|

Quarantine During COVID-19 Outbreak: Eating Behavior, Perceived Stress, and Their Independently Associated Factors in a Brazilian Sample

Abstract: The study aimed to assess the eating behavior [uncontrolled eating (UE), emotional eating (EE), and cognitive restraint (CR)], the perceived stress, and independently associated factors among Brazilians during the COVID-19 pandemic. An online survey was conducted and data about 1,368 participants were evaluated. Multivariate logistic regression models were performed to identify factors independently associated (socioeconomic, lifestyle, and eating habits data) with eating behaviors and perceived stress. Workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 46 publications
1
17
0
2
Order By: Relevance
“…Socioeconomic data (age, gender, home state, per capita income, education level, home residents); labor situation and social isolation occurred by the pandemic; eating behaviors (assessed by Three-Factor Eating Questionnaire) ( 15 ); perceived stress (assessed by Perceived Stress Scale) ( 16 ); eating habits (meals, food intake, snacking, food delivery, cooking at home, food frequency) ( 17 ); and lifestyle (sleep, physical activity, smoke, alcohol, screen time) prior and/or during the COVID-19 pandemic were investigated as predictors of weight gain, according to Liboredo et al ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…Socioeconomic data (age, gender, home state, per capita income, education level, home residents); labor situation and social isolation occurred by the pandemic; eating behaviors (assessed by Three-Factor Eating Questionnaire) ( 15 ); perceived stress (assessed by Perceived Stress Scale) ( 16 ); eating habits (meals, food intake, snacking, food delivery, cooking at home, food frequency) ( 17 ); and lifestyle (sleep, physical activity, smoke, alcohol, screen time) prior and/or during the COVID-19 pandemic were investigated as predictors of weight gain, according to Liboredo et al ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…The association between emotional eating and psychological distress and emotional dysregulation has also been described during the second wave of the COVID-19 pandemic in young Italian adults, especially in women [ 51 ]. Furthermore, the Brazilian study showed an independent association between emotional eating and perceived stress during the quarantine related to the COVID-19 outbreak, while perceived stress was independently associated with changes in the way of working or studying, worse sleep quality, and younger age [ 52 ]. Poor sleep quality and younger age as the risk factors of emotional eating were also described in the Turkish population [ 53 ].…”
Section: Emotional Eating During the Covid-19 Pandemicmentioning
confidence: 99%
“…It has been reported that perceived stress was significantly associated with emotional eating (43,44) . Liboredo et al stated that the participants snacked more frequently and increased their food intake during the quarantine period (44) . In the study conducted in Turkey; it was observed that https://doi.org/10.1017/S1368980022002579 Published online by Cambridge University Press Accepted manuscript the majority of the participants had changes in their emotional states such as anxiety, stress, and irritability after COVID-19, and these changes increased their food intake (45) .…”
Section: Accepted Manuscriptmentioning
confidence: 99%